Age and significance of voluminous mafic-ultramafic magmatic events in the Murchison Domain, Yilgarn Craton - Ivanic, T.; Wingate, M.; Kirkland, Chris; van Kranendonk, M.; Wyche, S. (Taylor & Francis Co Ltd, 2010)
Mafic-ultramafic rocks in structurally dismembered layered intrusions comprise approximately 40% by volume of greenstones in the Murchison Domain of the Youanmi Terrane, Yilgarn Craton. Mafic- ultramafic rocks in the Murchison Domain may be divided into five components: (i) the ~2810 Ma Meeline Suite, which includes the large Windimurra Igneous Complex; (ii) the 2800±6 Ma Boodanoo Suite, which includes the Narndee Igneous Complex; (iii) the 2792±5 Ma Little Gap Suite; (iv) ~2750 Ma Gnanagooragoo Igneous Complex; and (v) the 2735-2710 Ma Yalgowra Suite of layered gabbroic sills. The intrusions are typically layered, tabular bodies of gabbroic rock with ultramafic basal units which, in places, are more than 6 km thick and up to 2500 km2 in areal extent. However, these are minimum dimensions as the intrusions have been dismembered by younger deformation. In the Windimurra and Narndee Igneous Complexes, discordant features and geochemical fractionation trends indicate multiple pulses of magma. These pulses produced several megacyclic units, each ~200 m thick. The suites are anhydrous except for the Boodanoo Suite, which contains a large volume of hornblende gabbro. They also host significant vanadium mineralisation, and at least minor Ni-Cu-PGE mineralisation. Collectively, the areal distribution, thickness and volume of mafic-ultramafic magma in these complexes is similar to that in the 2.06 Ga Bushveld Igneous Complex, and represents a major addition of mantle-derived magma to Murchison Domain crust over a 100 Ma period. All suites are demonstrably contemporaneous with packages of high-Mg tholeiitic lavas and/or felsic volcanic rocks in greenstone belts. The distribution, ages and compositions of the earlier mafic-ultramafic rocks are most consistent with genesis in a mantle plume setting. © 2010 Geological Society of Australia.